Spatiotemporal evaluation of Social Vulnerability in urban spaces in Brazil: a proposal considering the city of Cuiabá, MT, Brazil - Neto, Aristóteles Teobaldo; Amorim, Margarete Cristiane de Costa Trindade [UNESP] (Universidade Federal do Paraná, 2022)
Risk has become an imperative in modern society, but the effects thereof are unequal in a class-based society marked by profound inequalities. Which, where and how many are the social groups most likely to suffer damage in the face of a hazardous event of any kind? What are the variables that most determine social vulnerability? To answer such questions, the main objective of this study was to adapt the SoVI (Social Vulnerability Index)® to spatiotemporally evaluate social vulnerability in Brazilian urban spaces. The proposed method was first applied in the city of Cuiabá, state of Mato Grosso (MT), Brazil. The results showed that social vulnerability in Cuiabá-MT is defined, in order of relevance, by the occurrence of low income; black/pardo population; education deficiency; low life expectancy, and children in the household. About 42.3% of the studied population are living in sectors with a high Urban SVI. The geography of social vulnerability in Cuiabá has a strong peripheral feature. The fact that the database used covers the entire Brazilian territory with data collected on a ten-year periodicity makes the proposed method feasible to be applied in urban areas of the whole country, favoring comparative spatial and temporal analyses. From a Latin American perspective, the present study intends to contribute to the international scientific debate on the reduction of risks, disasters and vulnerabilities.
Avaliação espaço-temporal da Vulnerabilidade Social nos espaços urbanos do Brasil: uma proposta a partir de Cuiabá-MT
Keywords: Principal Component Analysis; Risk; Vulnerability